A Study on Bacteriological Measurement of Clean Water in Raja Ampat - Linda Yanti Juliana Noya; Yura Witsqa Firmansyah (ECOTAS, 2023)
The availability of clean water is a right that must be obtained by all humans. Unfortunately, some water sources in Indonesia are polluted by total coliform and Escherichia coli and threaten health. This study aims to measure total coliform and Escherichia coli in the Weisai sub-district, Raja Ampat Regency, West Papua province as an effort to monitor environmental quality. This research is an observational study with a quantitative approach. Primary data in this study is the measurement of total coliform and Escherichia coli. The samples used were clean water in the borehole well of Bambang Sutejo village (T1); the dug well of Nyonya Fransina village (T2); and the dug well of Om Miter village (T3). Sample testing was conducted by the Environmental Health and Disease Control Technical Center (BTKLPP), Ambon City, and taken on November 28, 2022. The test results obtained, total coliform parameters of 1,600 MPN/100 mL and Escherichia coli 2.2 at T1. Meanwhile, the T3 concentration of total coliform and Escherichia coli exceeded 1,600 MPN/100 mL. T1 and T3 have values that exceed quality standards. This is due to livestock waste that does not have a wastewater disposal channel and the absence of communal domestic wastewater disposal channels